Correlation of morphological and functional indicators with sports results among qualified athletes specializing in freestyle swimming at distances of various lengths - Pilipko, O.; Pilipko, A. (Slobozhanskyi herald of science and sport, 2019)
Purpose: determine the degree of correlation between morphological and functional indicators and athletic performance among qualified athletes specializing in freestyle swimming at distances of various lengths.